Palatability status and animals’ preferences of forage plants in Pashat Valley, Pak-Afghan border, District Bajaur, Pakistan - Haq, Aminul; Badshah, Lal (Ethnobotany Research and Applications, 2023)
Background: The phytodiversity of a given region provide a variety of services to human and their livestock such as food, feed and medicines. The livestock’s preference and nutritional requirement are quantified by the plants’ palatability. The present study is the first attempt to record the palatable status of plant resources in the area. Objectives: The objective of this study was to assess the palatability of the flora and the preference of grazing and browsing animals in the Pashat Valley Bajaur, Khyber Pakhtunkhwa, Pakistan. Methods: An investigation survey with frequent visits to the research area in different seasons was conducted to record the palatability status of plant resources through visual observations of grazing animals. Results: The flora of Pashat Valley consists of 385 species belonging to 292 genera and 100 families. Based on habit, there were 289 species of herbs, 54 shrubs, 38 trees and 4 lianas. Of the recorded species, 98 species were non-palatable, 95 species were moderately palatable, 78 species were highly palatable, 60 species were less palatable and 54 species were rarely palatable. The animals preferred 187 plant species in fresh form while 92 species in both fresh and dry forms. Goats and sheep were found the prefer the majority of plant species. The seasonal availability reveals that most of the species grew in the spring (40.65 %) and summer (34.48%) seasons in the area. Conclusion: It was concluded that the area has a diverse flora with a rich source of palatable plants. Several variables influence the palatability such as plant morphology, phenology and chemical nature of plants. The documented data explore the palatability status which will act as the foundation for subsequent research into the nutritional components of the palatable plants that will be used as animal feed by the locals to satisfy their nutritional requirements. Keywords: Palatability, animals’ preference, grazing, browsing